Analisis Faktor-Faktor Behavioral Intention Mahasiswa menggunakan Kendaraan Listrik dengan Pendekatan Extending The Unified Theory Of Acceptance And Use Of Technology 2 (UTAUT2) - Ian, Muhammad Rezki; Nuromavita, Inka; Apriliyanto, Yohandika Tri (Jurnal Aplikasi Teknik Sipil, 2025)
The purpose of this study is to determine the factors that influence students towards Behavioral Intention or adoption of EV technology. Poor air quality caused by high transportation activities and exhaust emissions is an environmental problem faced by D.I Yogyakarta. The reason is the increase in educational potential which resulted in the number of students increasing by 0.97% from the previous year. Electric Vehicles (EVs) represent one of the solutions to this issue. Data collection by distributing questionnaires to 400 respondents at a confidence level of 95% using a disproportionate stratified random sampling technique. The model and theory approach used is the Unified Theory of Acceptance and Use of Technology2 (UTAUT2). The analysis results indicate that out of the 7 variables examined, several play a significant role in influencing students' behavioral intentions toward using electric vehicles, there are 4 significant variables, namely Performance Expectancy, Facilitating conditions, Hedonic motivation and Habits.